Potential Antioxidant Properties of Enzymatic Hydrolysates from Stichopus japonicus against Hydrogen Peroxide-Induced Oxidative Stress - Hyo-Geun Lee; Hyun-Soo Kim; Jae-Young Oh; Dae-Sung Lee; Hye-Won Yang; Min-Cheol Kang; Eun-A Kim; Nalae Kang; Junseong Kim; Soo-Jin Heo; You-Jin Jeon (Antioxidants, 2021)
A comprehensive antioxidant evaluation was performed on enzymatic hydrolysates of Stichopusjaponicus (S. japonicus) using Vero cells and zebrafish models for in vitro and in vivo studies, respectively. S. japonicus was hydrolyzed with food-grade enzymes (alcalase, α-chymotrypsin, flavourzyme, kojizyme, neutrase, papain, pepsin, protamex, and trypsin), and the free radical scavenging activities were screened via electron spin resonance (ESR) spectroscopy. According to the results, the enzymatic hydrolysates contained high protein and relatively low polysaccharide and sulfate contents. Among these hydrolysates, the α-chymotrypsin assisted hydrolysate from S. japonicus (α-chy) showed high yield and protein content, and strong hydroxyl radical scavenging activity. Therefore, α-chy was chosen for further purification. The α-chy was fractionated by ultrafiltration into three ultrafiltration (UF) fractions based on their molecular weight: >10 kDa (α-chy-I), 5–10 kDa (α-chy-II), and <5 kDa (α-chy-III), and we evaluated their antioxidant properties in H2O2 exposed Vero cells. The α-chy and its UF fractions significantly decreased the intracellular reactive oxygen species (ROS) generation and increased cell viability in H2O2 exposed Vero cells. Among them, α-chy-III effectively declined the intracellular ROS levels and increased cell viability and exhibited protection against H2O2 induced apoptotic damage. Furthermore, α-chy-III remarkably attenuated the cell death, intracellular ROS and lipid peroxidation in H2O2 exposed zebrafish embryos. Altogether, our findings demonstrated that α-chy and its α-chy-III from S. japonicus possess strong antioxidant activities that could be utilized as a bioactive ingredient for functional food industries.